(NkATALOG IZMERENIJ LU^EWYH SKOROSTEJ ZWEZD(B. (NkATALOG SOBSTWENNYH DWIVENIJ (B:s [(NsBORNIK(B] /s - (NtOKOWININ(B, (NaNDREJ aWRELIEWI^s ((NmOSKWA (B:s (Nmgu(B,s, 1990)
(NbIBLIOGR(B. (NW KONCE ST(B.s
(Nmgu IM(B. (Nm(B.(Nw(B. (NlOMONOSOWAs
Keywords: (NzWEZDNAQ DINAMIKAs; (NzWEZDYs; (NkATALOGIs